2015
DOI: 10.1021/acs.jproteome.5b00681
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics of Circular Cysteine-Rich Plant Peptides: Analysis of the Diversity of Cyclotides from Viola tricolor by Transcriptome and Proteome Mining

Abstract: Cyclotides are plant-derived mini proteins. They are genetically encoded as precursor proteins that become post-translationally modified to yield circular cystine-knotted molecules. Because of this structural topology cyclotides resist enzymatic degradation in biological fluids, and hence they are considered as promising lead molecules for pharmaceutical applications. Despite ongoing efforts to discover novel cyclotides and analyze their biodiversity, it is not clear how many individual peptides a single plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 63 publications
5
117
0
Order By: Relevance
“…Historically, cyclosporine A was instrumental to the development of modern immunopharmacology and it is still in clinical use today (29,36). Despite the limitations of such comparisons, we believe that the rich diversity of cyclotides (17,43) justifies their position as a treasure trove for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, cyclosporine A was instrumental to the development of modern immunopharmacology and it is still in clinical use today (29,36). Despite the limitations of such comparisons, we believe that the rich diversity of cyclotides (17,43) justifies their position as a treasure trove for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…[28] In a recent study, the use of in silico transcriptomic and proteomic screening identified 164 cyclotides in Viola tricolor , which led to the authors of this study to estimate the total number of cyclotides in the Violaceae family alone to be around 150,000. [29] In silico mining of genomes combined with molecular biology approaches has been used for the discovery of a large number of new ribosomal natural products, including cyclotides. [27] For example, database mining approaches were recently for the identification of cyclotide-like sequences in the plant Zea mays (maize), that were later confirmed to be expressed at the mRNA level in the root system of the plant.…”
Section: Discoverymentioning
confidence: 99%
“…29 In a recent study, the use of in silico transcriptomic and proteomic screening identified 164 cyclotides in Viola tricolor , which led to the authors of this study to estimate the total number of cyclotides in the Violaceae family alone to be around 150,000. 30 The CyBase database was recently created to allow easy access to the large number of cyclotide sequences that have been found thus far. 31 This database can be accessed through a publicly available website (http://CyBase.org.au) and contains above 300 known cyclotides as well as useful proteomic tools for their analysis.…”
Section: Discovery and Distributionmentioning
confidence: 99%